Influence of hydrogen on the microstructure and fracture toughness of friction stir welded plates of API 5L X80 pipeline steel - Hoyos, J. J.; Masoumi, M.; Pereira, V. F.; Tschiptschin, A. P.; Paes, M. T.P.; Avila, J. A. [UNESP] (Elsevier, 2019)
In this work, the influence of hydrogen on the microstructure and fracture toughness of API 5L X80 high strength pipeline steel welded by friction stir welding was assessed. Samples were hydrogenated at room temperature for a duration of 10 h in a solution of 0.1 M H2SO4 + 10 mg L−1 As2O3, with an intensity current of 20 mA cm−2. Fracture toughness tests were performed at 0 °C in single-edged notched bending samples, using the Critical Crack Tip Opening Displacement (CTOD) parameter. Notches were positioned in different regions within the joint, such as the stir zone, hard zone, and base material. Hydrogen induces internal stress between bainite packets and ferrite plates within bainite packets. Besides, hydrogen acted as a reducer of the strain capacity of the three zones. The base metal had a moderate capacity to resist stable crack growth, displaying a ductile fracture mechanism. While the hard zone showed a brittle behavior with CTOD values below the acceptance limits for pipeline design (0.1–0.2 mm). The fracture toughness of the stir zone is higher than that of the base metal. Nevertheless, the stir zone displayed higher data dispersion due to its high inhomogeneity. Hence, it can also show a brittle behavior with critical CTOD values.
Keywords: Friction stir welding; High strength steel; Hydrogen embrittlement; ISO 3183 X80 M